Detailed measured air speed distribution in four commercial buildings with ceiling fans. (August 2021) - Luo, Maohui; Zhang, Hui; Raftery, Paul; Zhou, Linxuan; Parkinson, Thomas; Arens, Edward; He, Yingdong; Present, Elaina
Abstract: The layout of ceiling fans in buildings is challenging because of the need to co-ordinate with other elements in the ceiling space, and because the resulting airflows within the occupied space interact with furniture. This study conducted detailed air speed measurements in four buildings with different room sizes, furniture configurations, ceiling fan types, and ceiling-fan-to-floor-area ratios. We measured air speeds across the occupied spaces at four heights while varying ceiling fan operation modes such as fan rotational speed, operating direction, and the number of operating fans. In total, we collected 207, 080 air speed samples at 343 sites under 20 test conditions. This paper presents the magnitude and distribution of air speeds, cooling effects, and their influencing factors. The Airspeed Coverage Index ( ACI = F a n a i r s p e e d ( S F ) × F a n d i a m e t e r ( D ) A v e r a g e a r e a s e r v e d p e r c e i l i n g f a n ( A ) ) describes the combined effects of multiple influencing factors on the magnitude of air speed. ACI is employed to predict the average air speed and occupant cooling effect, yielding regression confidences higher than 0.95. When designing a space to a target airspeed or cooling effect, the ACI can help to determine parameters such as fan density required for fan choices. The measured data are compared with predictions from the CBE fan tool that had been developed from laboratory tests under simplified conditions. The comparison displays the blocking effects of the furniture, lowering the average air movement in the space, as well as reducing the air movement at the ankle level while increasing it at higher heights. The blocking effect increases with the density of the furniture. We also visually present fan interactions in which triplets of fans are arranged linearly or diagonally, showing that the diagonal layout of ceiling fans increases average air speed and improves its uniformity. Highlights: Air speed distribution in four commercial buildings with ceiling fans are studied. The Airspeed Coverage Index is employed to predict the average air speed and cooling effects. Downward operating fans have higher air speeds while upward operating fan has better uniformity. The higher density of the furniture, the stronger the blocking effects will be. The layout of ceiling fans can influence the magnitude and uniformity of air speeds in a space.